ByzRev 04.2022.006: Gunnel Ekroth – Ingela Nilsson (eds.), Round Trip to Hades in the Eastern Mediterranean Tradition: (Cultural Interactions in the Mediterranean 2). Leiden – Boston: Brill 2018. - Murace, Andrea (The Byzantine Review, 2022)
Gunnel Ekroth – Ingela Nilsson (eds.), Round Trip to Hades in the Eastern Mediterranean Tradition (Cultural Interactions in the Mediterranean 2). Leiden – Boston: Brill 2018. XVII, 397 pp., 39 figg., 2 tabb. – ISBN 978-90-04-37266-5 (€137.00, 165.00)